2012
DOI: 10.1186/scrt104
|View full text |Cite
|
Sign up to set email alerts
|

Orthopaedic applications of nanoparticle-based stem cell therapies

Abstract: Stem cells have tremendous applications in the field of regenerative medicine and tissue engineering. These are pioneering fields that aim to create new treatments for disease that currently have limited therapies or cures. A particularly popular avenue of research has been the regeneration of bone and cartilage to combat various orthopaedic diseases. Magnetic nanoparticles (MNPs) have been applied to aid the development and translation of these therapies from research to the clinic. This review highlights con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 89 publications
0
29
0
Order By: Relevance
“…They reported that cell attachment and distribution were improved on chitosan coated with type Ⅱ collagen. A study of the effect of growth factors on the proliferation of MSCs encapsulated in a hydrogel scaffold was also reviewed and TGFβ3 was from research to the clinic [61] . Characterization of cell localization and associated tissue regeneration can be enhanced, particularly for in vivo applications.…”
Section: Scaffold As a Carriermentioning
confidence: 99%
“…They reported that cell attachment and distribution were improved on chitosan coated with type Ⅱ collagen. A study of the effect of growth factors on the proliferation of MSCs encapsulated in a hydrogel scaffold was also reviewed and TGFβ3 was from research to the clinic [61] . Characterization of cell localization and associated tissue regeneration can be enhanced, particularly for in vivo applications.…”
Section: Scaffold As a Carriermentioning
confidence: 99%
“…Currently, scientists have focused on the application of nanomaterials in the stem cell biology, due to their ability to control the function of stem cells, and also in tissue regeneration, due to their chemical, physical or biological properties and biomimetic characteristics in particular. [8][9][10][11][12] In this review, we have focused on iPSCs, ESCs, the properties and studies on in vitro and in vivo clinical application of nanomaterials (Fig. 3).…”
Section: Introductionmentioning
confidence: 99%
“…One application is the use of nanomagnetic actuation for the mechanical conditioning of cells in tissue engineering and regenerative medicine. 4 Several studies have reported their successful application in orthopaedics. 56 The principle of pediatric endodontics in primary dentition is that tooth should remain in mouth in a nonpathological healthy condition to fulfill its role in primary and mixed dentition.…”
Section: Introductionmentioning
confidence: 99%